Healthcare-associated Staphylococcus aureus infections in children in Turkey: A six-year retrospective, single-center study - SAYIN, ELVAN; İLKİ, ZEYNEP ARZU; KEPENEKLİ KADAYİFCİ, EDA (My University, 2023)
Objective: To describe clinical and epidemiological characteristics, antimicrobial susceptibility and mortality-associated factors of healthcare-associated infections (HCAIs) caused by Staphylococcus (S.) aureus in children. Methods: We conducted a retrospective, single-centre study of pediatric HCAIs caused by S. aureus from a tertiary care hospital in Turkey between February 2014 and December 2019. The clinical and epidemiological characteristics and antimicrobial susceptibility of the methicillin-susceptible and methicillin-resistant S. aureus (MSSA and MRSA) isolates was evaluated. Results: A total of 310 pediatric patients were examined. Overall, 225 (72.6%) isolates were MSSA and 85 (27.4%) were MRSA. All S. aureus isolates were susceptible to teicoplanin, vancomycin, linezolid, tigecycline, mupirocin, and daptomycin. Penicillin resistance rates were high (89.0%), while fosfomycin, gentamicin, and clindamycin resistance rates were low (1.3%, 1.0%, and 2.3%, respectively). Except susceptibility to fosfomycin, which was significantly lower in 2014 compared to 2018 and 2019, no significant difference was found in the antimicrobial susceptibility of S. aureus isolates between the years. Baseline characteristics and mortality rate were similar comparing MRSA and MSSA causing HCAIs. The mortality rate of HCAIs caused by S. aureus was 6.5% (20 patients). Malignancy was an independent risk factor associated with mortality in the multivariate analysis (OR 5.446, 95% CI 1.573- 18.849). Conclusions: Our findings demonstrate that MSSA remained the most causative agent of HCAIs caused by S. aureus. The mortality rate was 6.5%, the antibiotic resistance rate was quite high for penicillin and diagnosis of malignancy was the main risk factor for increasing mortality in children. These findings could help improve the management of HCAIs caused by S. aureus in children.
Keywords: Tıp; Mikrobiyoloji ve Klinik Mikrobiyoloji; Tıbbi Mikrobiyoloji; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Pediatrik Enfeksiyon; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Microbiology and Clinical Microbiology; Medical Microbiology; Internal Medicine Sciences; Child Health and Diseases; Pediatrics Infectious Diseases; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Mikrobiyoloji; PEDİATRİ; TIP, GENEL & DAHİLİ; MİKROBİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MICROBIOLOGY; PEDIATRICS; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Pediatri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Pediatri, Perinatoloji ve Çocuk Sağlığı; Mikrobiyoloji (tıbbi); Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; İmmünoloji ve Mikrobiyoloji (çeşitli); Yaşam Bilimleri; General Health Professions; Pediatrics; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Pediatrics, Perinatology and Child Health; Microbiology (medical); Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Microbiology; Immunology and Microbiology (miscellaneous); Life Sciences; Healthcare-associated infections; Staphylococcus aureus; Children; Antimicrobial susceptibility; Mortality